2017
DOI: 10.1016/j.parint.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, molecular characterization, and in vitro schizogonic development of Sarcocystis sp. ex Accipiter cooperii from a naturally infected Cooper's hawk (Accipiter cooperii)

Abstract: Raptors serve as the definitive host for several Sarcocystis species. The complete life cycles of only a few of these Sarcocystis species that use birds of prey as definitive hosts have been described. In the present study, Sarcocystis species sporocysts were obtained from the intestine of a Cooper's hawk (Accipiter cooperii) and were used to infect cell cultures of African green monkey kidney cells to isolate a continuous culture and describe asexual stages of the parasite. Two clones of the parasite were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…With respect to the three regions of the nuclear ribosomal DNA unit examined, this study again showed that Sarcocystis spp. with avian intermediate hosts can only be unambiguously delimited on the basis of sequences of the ITS1 region, whereas they are identical or nearly identical at the complete 18S rRNA gene, and almost identical in the portion of the 28S rRNA gene (D2/D3 domain) that is usually examined ( Prakas et al, 2014 , Lindsay et al, 2017 ). This study provided for the first time partial cox1 sequences of S. halieti and S. lari .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the three regions of the nuclear ribosomal DNA unit examined, this study again showed that Sarcocystis spp. with avian intermediate hosts can only be unambiguously delimited on the basis of sequences of the ITS1 region, whereas they are identical or nearly identical at the complete 18S rRNA gene, and almost identical in the portion of the 28S rRNA gene (D2/D3 domain) that is usually examined ( Prakas et al, 2014 , Lindsay et al, 2017 ). This study provided for the first time partial cox1 sequences of S. halieti and S. lari .…”
Section: Discussionmentioning
confidence: 99%
“…JQ733511 – JQ733513 ). Likewise, in a recent study from the United States, a Cooper's hawk ( Accipiter cooperii ) was found to act as definitive host of an unnamed species that was genetically most closely related to S. columbae ( Lindsay et al, 2017 ). In an earlier study from the USA, Yabsley et al (2009) obtained sequences of the partial 18S ribosomal (r) RNA gene from 10 intestinal samples from four species of hawks harbouring Sarcocystis oocysts/sporocysts, and found seven slightly different sequence variants (GenBank nos.…”
Section: Introductionmentioning
confidence: 99%
“…have strict host demand that their development needs to be completed in two hosts (Dubey et al, 1989). The parasites reproduce asexually in their intermediate hosts, such as herbivores, omnivorous animals, and birds (Dahlgren & Gjerde, 2008;Lindsay et al, 2017). Then the protozoan would finish the sexual part of their life cycle in the definitive hosts which are carnivorous animals like dogs, wolves, cats, and human beings (Yang et al, 2001;da Silva et al, 2009;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal tract was removed, refrigerated at 4 C, and transported to the Zoonotic Protozoal Diseases Laboratory at the Virginia Maryland College of Veterinary Medicine, Blacksburg, Virginia. Sporocysts were collected separately from the intestinal scrapping of the RTH using methods described previously (Lindsay et al, 2017). Some of these sporocysts were used to attempt in vitro culture in African green monkey kidney (CV-1) cells using methods previously described (Lindsay et al, 2017).…”
mentioning
confidence: 99%
“…Sporocysts were collected separately from the intestinal scrapping of the RTH using methods described previously (Lindsay et al, 2017). Some of these sporocysts were used to attempt in vitro culture in African green monkey kidney (CV-1) cells using methods previously described (Lindsay et al, 2017). Excystation occurred, and schizonts were observed developing in CV-1 cells within 2 wk, but the culture died out and was discarded after 2 mo of observations.…”
mentioning
confidence: 99%